IMPLEMENTASI PENDIDIKAN KEWIRAUSAHAAN DI SMA NEGERI 1 PEKANBARU DAN DAMPAKNYA TERHADAP KREATIVITAS PESERTA DIDIK - R. Wenmar Isqaedah; Zulfan Saam; Makhdalena Makhdalena (Universitas Riau, 2020)
This research is a qualitative research that aims to about the implementation of entrepreneurship education in SMA Negeri 1 Pekanbaru and its impact on the creativity of learners. Formulation of the problem in this study as follows: 1). How is the characteristic of entrepreneurship education in SMA Negeri 1 Pekanbaru, 2). How is the implementation implementation of entrepreneurship education in SMA Negeri 1 Pekanbaru, 3). How the impact of the implementation of entrepreneurship education on the Creativity of learners in SMA Negeri 1 Pekanbaru. The data collection of this research is done by observation, interview, lapanagn record and documentation with the implementation model used is Mazmanian and Sabatier Model. The results of this study reveal some findings are: 1). Characteristics of entrepreneurship education in SMA Negeri 1 Pekanbaru is still not maximized and needs to be improved. This is because the implementation of entrepreneurship education is still a lot for the scope of handicrafts, 2). Judging from the implementation of the implementation of entrepreneurship education in SMA Negeri 1 Pekanbaru has not been maximized. This is reflected in the successful implementation of the education has not reached the desired goals. Attitudes and behaviors of entrepreneurial entrepreneurs and school environment with entrepreneurial insight need to be improved, 3). The impact of the implementation of entrepreneurship education on the creativity of students in SMA Negeri 1 Pekanbaru has not been maximized. The implementation or practice of learning in the classroom for the subject of Workshop and Entrepreneurship (PKWU) needs variation, creativity and improvement.